Australia's American coffee culture. Issue 1 (7th June 2012) - Adams, Jill
When US coffee chain Starbucks announced it would close 61 of its 84 Australian stores, some Australian coffee drinkers were smug: Starbucks, it seemed, had failed to understand the Australian market. The President of Starbucks Asia Pacific John Culver admitted: 'I think what we've seen is that Australia has a very sophisticated coffee culture'. Australia does have a sophisticated coffee culture and the collective belief is that its origins are European. This article argues that Australia had a coffee culture of sorts prior to WWII but that it was American serviceman stationed in Australia, followed closely by the introduction of Nestlé instant coffee in 1948, that kick-started Australia's shift from tea to coffee drinking. It also argues that Australia's contemporary coffee market is very similar to America's, with recent trends in America's specialty coffee industry closely watched and followed by Australian 'third wave' coffee roasters and consumers.